Changing rural economy of Bangladesh - Mandal, M. A. S.; Bangladesh Economic Association (Dhaka : Bangladesh Economic Association, 2000)
Contributed articles presented at a regional seminar in 1997.
Includes bibliographical references.
Keywords: Rural development -- Bangladesh; Bangladesh -- Economic conditions; Bangladesh -- Social conditions